2022
DOI: 10.3389/fimmu.2021.779119
|View full text |Cite
|
Sign up to set email alerts
|

ADAM Metalloproteinase Domain 17 Regulates Cholestasis-Associated Liver Injury and Sickness Behavior Development in Mice

Abstract: Disintegrin and metalloproteinase domain-containing protein 17 (ADAM17) is a ubiquitously expressed membrane-bound enzyme that mediates shedding of a wide variety of important regulators in inflammation including cytokines and adhesion molecules. Hepatic expression of numerous cytokines and adhesion molecules are increased in cholestatic liver diseases including primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC), however, the pathophysiological role of ADAM17 in regulating these conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…To the best of our knowledge, no study has reported the association of ADAMTS family members with cholestasis. However, a close relative of the ADAMTS family, ADAM17, has been reported to be related to cholestasis ( 43 ). Increased ADAM17 expression was found in patients with two important cholestatic liver diseases, including primary biliary cholangitis and primary sclerosing cholangitis ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no study has reported the association of ADAMTS family members with cholestasis. However, a close relative of the ADAMTS family, ADAM17, has been reported to be related to cholestasis ( 43 ). Increased ADAM17 expression was found in patients with two important cholestatic liver diseases, including primary biliary cholangitis and primary sclerosing cholangitis ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was performed on the slides as described. 10 In brief, endogenous peroxidase activity was inhibited with 3% hydrogen peroxide. The slides were then blocked with 4% goat serum before being incubated with a primary mouse antibody against SARS-CoV-2 (GeneTex GTX632604, Clone1A9) overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Mice lacking Timp3 , a specific endogenous inhibitor of ADAM17 activity, serve as a model of ADAM17 gain of function, and exhibit hepatic lymphocyte infiltration and necrosis, mainly due to constitutive ADAM17‐dependent TNFα signaling in the liver [60]. Moreover, pharmacologic inhibition of ADAM17 using the selective small molecule inhibitor DPC‐333 ameliorated liver injury in a bile duct ligation‐induced mouse model of cholestatic liver injury [61].…”
Section: Adam17 In Inflammatory Conditionsmentioning
confidence: 99%